EXPLORING THE SIGNIFICANCE OF THEME IN STYLISTICS: UNRAVELING THE INTRICACIES OF MEANING AND COMMUNICATION - Mamirova Shahnoza Qahramon qizi; Zilola Abduraxmonova (TADQIQOTLAR.UZ, 2023)
Abstract: This article delves into the field of stylistics, with a specific focus on the concept of theme. Theme, a fundamental aspect of language and discourse, plays a crucial role in shaping meaning and communication. By analyzing the distribution and manipulation of theme in various texts, researchers can uncover the intricacies of how themes contribute to the overall stylistic effect. This article provides an overview of the key concepts and methodologies employed in studying theme in stylistics and highlights its significance in unraveling the complexities of meaning and communication.